Isolation and Identification of Some Pathogenic Bacteria from Otitis Media in Babylon Governorate - Hawraa Jawad Kadhim (Journal of Global Pharma Technology, 2018)
This study was conducted for the period from February to November 2016 in Babylon Teaching Hospital , during this period, 200 swab ear of people with otitis media in the city of Babylon were collected . 120 sample was diagnosed with bacterial isolates depending on morphology on the different culture media and some biochemical tests. The highest rate of infection in the age group (21-40)years , and the least in the age group (41-60)years as it was(46 %,15%)respectively. In this study were isolate five types of a bacteria (Pseudomonas aeruginosa, Staphylococcus aureus , Escherichia coli, Streptococcus pneumonia and Klebsiella pneumonia) and the highest rate of infection has reached (35 %, Pseudomonas aeruginosa), ( 26%,Staphylococcus aureus). As for the results of examination of the sensitivity of the bacterial isolates to antibiotics was the highest rate of antibiotic resistance was (94%Tetracyclin, 92%Ampicilin and 91% Chloramphenicol), while the resistance decreased in the case of antibiotics (42%Amikacin, 42%Gentamicin and 31%Tobramycin). Streptococcus pneumonia were detected by PCR , 16 cases were PCR positive for Streptococcus pneumonia , there was no samples displayed culture positive and PCR negative for Streptococcus pneumonia .Keywords: Pathogenic bacteria, Otitis media, Sensitivity test, PCR.